Hubungan Stres, Kualitas Tidur, dan Fatigue dengan Kualitas Hidup Pasien Gagal Jantung di RSUD Ahmad Yani - Siti Elma Zaira; Tubagus Erwin Nurdiansyah; Aulia Rahman (Universitas Nurul Jadid, 2026)
Patients with chronic heart failure often experience various worsening symptoms that are not well-identified in healthcare services, including sleep quality. Decreased quality of life is triggered by physical limitations, Fatigue, and psychological conditions such as stress and anxiety. As a primary indicator of morbidity, poor quality of life significantly increases the risk of disease progression, rehospitalization, and mortality. Therefore, monitoring quality of life is crucial as an early indicator in maintaining the survival of heart failure patients. This study aims to analyze the relationship between stress, sleep quality, and Fatigue with the quality of life of heart failure patients at the Cardiac Outpatient Clinic of RSUD Jend Ahmad Yani Metro. This quantitative study used a cross-sectional design involving 218 heart failure patients selected through purposive sampling. Data were collected using questionnaires, and bivariate analysis was conducted using the Chi-Square test. The majority of respondents (53.7%) had a low quality of life. Furthermore, 54.1% of patients reported poor sleep quality, and 55.5% experienced Fatigue. Statistical test results showed a significant relationship between stress (p=0.001), sleep quality (p=0.001), and Fatigue (p=0.001) with the quality of life in heart failure patients. These findings emphasize the importance for healthcare professionals, especially cardiovascular nurses, to not only focus on physiological medical parameters but also conduct routine screenings for sleep quality, Fatigue levels, and psychological status. Comprehensive nursing interventions—such as sleep management and stress coping strategy education—are essential to prevent a decline in quality of life, which ultimately reduces rehospitalization rates and increases the life expectancy of heart failure patients.